Efeitos do diabetes gestacional moderado e da reposição com insulina na lactação sobre a próstata ventral do rato Wistar - Santos, Sérgio Alexandre Alcantara dos [UNESP] (2014)
Diabetes mellitus (DM) is a clinical heterogenic, caused by beta-pancreatic cell deficiency of insulin synthesis or due to target cells-dysfunction in insulin receptor, resulting in hyperglycemic metabolic disease. When associated with pregnancy, diabetes can lead to increased risk for maternal/fetal. The maternal hyperglycemia stimulates the fetal outgrow due to higher blood-glucose levels and growth factors. The high birth weight is related to the risk of development insulin resistance, obesity and DM type 2 in adulthood. The diabetes also affects negatively male reproductive system, mainly accessory glands and gonads. Although the literature has been demonstrated the influence of diabetes on testicular functions and fertility, the impact of gestational diabetes on prostate morphogenesis and growth in male offspring is far to be elucidated. Thus, due to the clinical importance of thematic, the aim of this project was to evaluate the possible effects of mild gestational diabetes on the rat ventral prostate (VP) growth, maturation and function at post-natal day (PND) 60 and 120. It was investigate the general morphology, cell proliferation and apoptosis, androgen receptor localization and expression, as well as the prostatein, an androgen-stimulated secretory protein in the VP of male offspring from dams streptozotozin-induced moderated gestational diabetes. The serum testosterone and insulin showed no statistical difference between experimental groups. The VP relative weight increased in the offspring of mothers that received insulin during lactation (GDI) on PND120. Histologically, the VP from diabetic mother (D) showed a reduction in the lumen of acini and increased in prostatic fibromuscular stroma. Insulin replacement during lactation restored glandular morphology, although in the GDI group at PND120, the stroma remained thicker than that observed in the CT group. There is no difference in cell proliferation or apoptosis among